Stability of Viscoelastic Wave Equation with Structural $δ$-Evolution in $\mathbb{R}^{n}$ (Analysis in Theory and Applications, 2022)
The aim of this paper is to study the Cauchy problem for the viscoelastic wave equation for structural $δ$-evolution models. By using the energy method in the Fourier spaces, we obtain the decay estimates of the solution to considered problem.